The true Spinoza of Market Street. Issue 5 (28th May 2019) - Strawser, Michael
ABSTRACT: Spinoza is commonly viewed as a rationalist philosopher emphasising abstract metaphysical truth over concrete human emotions and relations. This view permeates Isaac Bashevis Singer's 'The Spinoza of Market Street', which ridicules the intellectualism of Dr Nahum Fischelson, who had studied Spinoza's Ethics 'for the last thirty years' and provocatively asked Spinoza's forgiveness for becoming a fool after consummating his marriage. But is love a thing for fools? Is it accurate to view Spinoza's philosophy in this way? Here I argue that Singer's view of Spinoza is a misleading caricature, for it fails to appreciate Spinoza's emphasis on emotional well-being, which clearly involves a recognition of love's binding force. Spinoza's perfectionist ethic not only allows for a life of love and emotional commitment, as in marriage, but it even goes further in showing us how noble love has the power to make us truly free. Ultimately, I argue that the true Spinoza of Market Street is not Dr Fischelson, but rather Black Dobbe, and that this reading rightly expresses the progressive nature of Spinoza's ethics of love and view of freedom.